Diffractaic acid, a novel proapoptotic agent, induces with olive oil both apoptosis and antioxidative systems in Ti-implanted rabbits - Odabasoglu, Fehmi; Yildirim, Omer S.; Aygun, Hayati; Halici, Zekai; Halici, Mesut; Erdogan, Fazli; Bayir, Yasin (Elsevier Science Bv, 2012)
Usnea longissima Ach., a lichen species, is a traditional herbal medicine with anti-detrimental effects. We evaluated the in vivo effects of a major constituent of U. longissima, diffractaic acid, and the main fatty component of the Mediterranean diet, olive oil, against apoptosis, including various caspase activations and oxidative injury in surrounding tissues after titanium implantation in rabbit femurs. Furthermore, we evaluated the underlying molecular mechanisms. In this study, this lichen metabolite and olive oil activated caspase-dependent cell death with apoptotic morphology, which is distinctly different from necrosis. Both orally and locally administered olive oil and diffractaic acid exerted pro-apoptotic induction in tissues surrounding the implants in titanium-implanted rabbits through the activation of initiator caspases (Cas-2, -8 and -9) and executioner caspase (Cas-3). In addition, they displayed strong myeloperoxidase and inducible nitric oxide synthase activities, providing an alleviating effect. Furthermore, administrations of diffractaic acid and olive oil attenuated the Ti-alloy implantation, and decreased superoxide dismutase activity and total glutathione level in pen-implant tissues. These results demonstrate that diffractaic acid and olive oil are involved in the induction of apoptotic cell death both through caspase-dependent cell death and as an antioxidant Thus, the data suggest that both diffractaic acid and olive oil could be developed as effective proapoptotic agents in various disorders treatments. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Diffractaic acid; Titanium alloy; Apoptosis; Caspase; Antioxidant; Olive oil